Arctic teacher education and educator training: a postcolonial review of online approaches and practices - Darling-McQuistan, Kirsten; Ekberg, Niclas; Snow, Kathy; Alerby, Eva; Curtis, Liz; Jannok-Nutti, Ylva (Luleå tekniska universitet, Pedagogik, språk och ämnesdidaktik, 2023)
Digitalisation, and expanding digital infrastructure has given rise to new pedagogical approaches and practises that involve making use of the internet. In the development of this literature-based article, we examined Arctic online education from a holistic perspective, adopting broad definitions of online learning environments and teacher education. The aim of this paper is to map and analyse the state of knowledge regarding the digital transformations of practices and conceptualisations in teacher education and educator training in the Arctic, as we sought to answer the following research question: What is Arctic in online teaching and learning in teacher education and educator training? Our methodology consisted of a scoping review of peer-reviewed papers published between 2003-2023. Through a qualitative content analysis, we explored definitions, perspectives and positions that emanated from the literature. Viewed through the lens of postcolonial theory, our findings and discussion surface important points of ‘difference’ (Verran, 2013) between Indigenous pedagogies, which are a central part of the Arctic-ness, and technological advances that enable online and distance learning, namely: Rootedness And Fluidity; Continuity of the Story And Fragmentation; Preservation And Transformation; Traditional Seeing And (Western) Frameworks, which we argue should be a key feature of conversations within this field. Godkänd;2023;Nivå 0;2023-12-28 (sofila); Funding: Danish Agency for Science and HigherEducation (DAFSHE); Full text license: CC BY-NC 4.0 Distance Teaching and Learning in the Arctic Communities (DistARCTIC)